Inhibitory effect of sea buckthorn extracts on advanced glycation endproduct formation. (30th March 2022) - Lee, Hyun Hee L; Lee, Chang Jun; Choi, Sang Yoon; Kim, Yoonsook; Hur, Jinyoung
Highlights: Sea Buckthorn leaf extracts inhibit the formation and crosslinking of AGEs. Ultra performance liquid chromatography results revealed 30 different AGE binding sites in bovine serum albumin. Sea buckthorn leaves extracts have a DPPH and ABTS radical scavenging activity. Abstract: This study shows the inhibitory effect of sea buckthorn ( Hippophae rhamnoides L . ) extracts, sea buckthorn leaf (HRL) and berry (HRB), on the formation of advanced glycation endproducts (AGEs), closely linked to diverse disease. In vitro assay revealed the superior inhibitory effect of HRL on the AGEs formation and AGEs-induced collagen crosslinking compared with that of HRB. Ultra-performance liquid chromatography-mass spectrometry results revealed that HRL displays a higher inhibition efficiency on the AGEs formation at 30 AGEs binding sites in bovine serum albumin than HRB. The high concentration of 3-sophoroside-7-rhamnoside in HRL compared with that in HRB may result in the strong inhibitory effect of HRL compared with that of HRB. HRL also exhibited significantly higher ABTS and DPPH radical scavenging activities than HRB. Overall, this study demonstrated that HRL has excellent potential as a dietary agent for controlling various diseases mediated by AGEs and oxidative stress.